Acceptability of COVID-19 Vaccine in Africa - Frankline Sevidzem Wirsiy; Ngwayu Claude Nkfusai; Denis Ebot Ako-Arrey; Esther Kenfack Dongmo; Florence Titu Manjong; Samuel Nambile Cumber (Global Health and Education Projects, Inc., 2021)
As Africa prepares to overcome the difficult challenges of COVID-19 vaccination roll-outs, a number of factors, including equitable access, effective and efficient sufficient supply chains, a scope of established determinants will need to be considered in order to enhance vaccine acceptability and uptake. In this commentary, we present six major determinants of vaccine acceptability and uptake in Africa. We summarize these determinants with the acronym VAMRIS: V= Vaccine hesitancy; A= Attitude and uptake by health care workers; M= Misinformation; R= Religion; I= Immunization roll out plans; S= Social influences and enabling environment. Understanding determinants of COVID-19 vaccine acceptability will guide public health officials make informed decisions. As the Vaccine becomes progressively available, strategies for efficient roll-out to achieve massive uptake by the targeted population will depend on a number of factors. These include: community engagement efforts; types of health promotion activities and/or messages; community sensitization to dispel myths and misconceptions; endorsements and buy-ins from local champions, celebrities, authorities; logistic considerations; and incentives to health counsellors/workers to create demand.   Copyright © 2020 Wirsiy et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.